2019
DOI: 10.3390/d11020025
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Habitat Usage of Juvenile Carnivorous Fish Among Seagrass-Coral Mosaic Habitats

Abstract: Seagrass beds and coral reefs are both considered critical habitats for reef fishes, and in tropical coastal regions, they often grow together to form “mosaic” habitats. Although reef fishes clearly inhabit such structurally complex environments, there is little known about their habitat usage in seagrass-coral mosaic habitats. The goal of this study was to examine potential factors that drive habitat usage pattern by juvenile reef fishes. We quantified (1) prey availability, (2) potential competitors, and 3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
1
9
0
2
Order By: Relevance
“…Lamun adalah tumbuhan berbunga yang hidup pada perairan pasang surut, berperan sebagai pelindung dan penstabil garis pantai (Christianen et al, 2013;Ondiviela et al, 2014), produsen primer (Erftemeijer et al, 1993), pensiklus nutrien (Erftemeijer & Middelburg, 1995), tempat proses biogeokimia (Thangaradjou et al, http://journal.ipb.ac.id/index.php/jurnalikt 2015), habitat makrofauna bentik (Junhui et al, 2018), habitat ikan (Erftemeijer & Allen, 1993;Phinrub et al, 2015 ), pembesaran ikan juvenil (Jones, 2014;McDevitt-Irwin et al, 2016;Jianguo et al, 2018), sumber makanan ikan juvenil (Nakamura et al, 2012;Kwak et al, 2015); sumber makanan langsung hewan herbivora (Scott et al, 2018); penghubung distribusi spasial ikan antar habitat (habitat ontogenetik) pada perairan pesisir (Campbell et al, 2011;Whitfield, 2017;Lee et al, 2019); pendukung stok perikanan (Unsworth et al, 2010), ketahanan pangan (Unsworth et al, 2014), sumber mata pencaharian nelayan (Syukur et al, 2017), dan mendukung kegiatan perikanan (subsisten, komersial dan rekreasi) global (De la Torre-Castro et al, 2014;Nordlund et al, 2018;Jeyabaskaran et al, 2018;Unsworth et al, 2019). Habitat padang lamun umumnya pada perairan pantai, estuari, daerah intertidal, subtidal sampai terumbu karang dengan beragam tipe substrat (Waycott et al, 2004).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Lamun adalah tumbuhan berbunga yang hidup pada perairan pasang surut, berperan sebagai pelindung dan penstabil garis pantai (Christianen et al, 2013;Ondiviela et al, 2014), produsen primer (Erftemeijer et al, 1993), pensiklus nutrien (Erftemeijer & Middelburg, 1995), tempat proses biogeokimia (Thangaradjou et al, http://journal.ipb.ac.id/index.php/jurnalikt 2015), habitat makrofauna bentik (Junhui et al, 2018), habitat ikan (Erftemeijer & Allen, 1993;Phinrub et al, 2015 ), pembesaran ikan juvenil (Jones, 2014;McDevitt-Irwin et al, 2016;Jianguo et al, 2018), sumber makanan ikan juvenil (Nakamura et al, 2012;Kwak et al, 2015); sumber makanan langsung hewan herbivora (Scott et al, 2018); penghubung distribusi spasial ikan antar habitat (habitat ontogenetik) pada perairan pesisir (Campbell et al, 2011;Whitfield, 2017;Lee et al, 2019); pendukung stok perikanan (Unsworth et al, 2010), ketahanan pangan (Unsworth et al, 2014), sumber mata pencaharian nelayan (Syukur et al, 2017), dan mendukung kegiatan perikanan (subsisten, komersial dan rekreasi) global (De la Torre-Castro et al, 2014;Nordlund et al, 2018;Jeyabaskaran et al, 2018;Unsworth et al, 2019). Habitat padang lamun umumnya pada perairan pantai, estuari, daerah intertidal, subtidal sampai terumbu karang dengan beragam tipe substrat (Waycott et al, 2004).…”
Section: Pendahuluanunclassified
“…Fenomena ini menunjukkan fungsi padang lamun sebagai daerah pembesaran. Menurut McDevitt-Irwin et al (2016) padang lamun dijadikan sebagai habitat pembesaran yang mendukung kepadatan, pertumbuhan atau kelangsungan hidup ikan juvenil dibandingkan habitat lainnya, sehingga mendukung distribusi spasial ikan antar habitat (habitat ontogenetik) pada perairan pesisir (Campbell et al, 2011;Honda et al, 2013;Whitfield, 2017;Lee et al, 2019).…”
Section: Distribusi Spasial Ikan Baronangunclassified
“…Because of isolation and military restriction, low human impact and less fishery pressure, Dongsha Island still has rather pristine seagrass beds and coral reefs. Coral reefs and seagrass beds are often mixed in the shallow waters around Dongsha Island, forming highly complex habitats [13]. Previous studies indicated high primary production as well as high biodiversity in the seagrass beds of Dongsha Island [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Coral reefs and seagrass beds are often mixed in the shallow waters around Dongsha Island, forming highly complex habitats [13]. Previous studies indicated high primary production as well as high biodiversity in the seagrass beds of Dongsha Island [13][14][15][16]. However, the energy flows of seagrass production within this tropical atoll remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Seagrass can increase pH by up to 0.4 (Unsworth et al, 2012) by reducing CO 2 through photosynthetic uptake (dependent on water residence time and water depth). Thus, seagrass could potentially buffer future ocean acidification (OA), thereby potentially modulating OA impacts on other members of the seagrass bed community, such as phytoplankton, benthic algae, or even corals in areas where seagrass and corals are located in proximity (Huan et al, 2015;Lin et al, 2018;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%